PELUANG DAN TANTANGAN KERJASAMA INDONESIA - KOREA SELATAN DALAM PEMBANGUNAN PEMBANGKIT LISTRIK TENAGA NUKLIR (PLTN) DI INDONESIA - Putri Herianasari; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the chancesand challenges on developing of Nuclear Power Plant in Indonesia.              The sources of this research were obtained through literature reviews, books, websites, and others. The source of analysis is qualitative methods. This study uses the level of analysis of the nation state, neo-liberalism perspective. The neoliberalization, cooperation for the country is an investment that will benefit the country. This is in accordance with the priorities of the neoliberalists as forming opportunist states, countries that provide a focus on pursuing absolute profits                the current source of electrical energy derived from fossils will be increasingly scarce given the limited natural resources of petroleum and coal, while the need for electricity is increasing. therefore the need for alternative energy sources to meet the needs of electrical energy which is increasingly fast. one of the energy sources that will be developed is nuclear power Keywords : Chances, and Challenges, on Developing of, Nuclear, Power Plants.